GEOMORPHIC EVOLUTION OF THE PALAMARI BAY (NORTHEASTERN SKYROS ISLAND) DURING LATE HOLOCENE - Παυλόπουλος, Κ.; Καρύμπαλης, Ε.; Καρκάνας, Π.; Παρλαμά, Λ.; Μάνος, Ι.; Τριαντάφυλλου, Μ.; Θεοχάρη, M. (Bulletin of the Geological Society of Greece, 2018)
Palamari bay is loceted on the northeastern coast of Skyros island (Sporades islands, Aegean sea). The area is of fundamental archaeological interest because of a prehistoric archaeological site, located at the northern part of the bay. In order to investigate the geomorphic evolution of the broader area a detailed geomorphological mapping of the coastal and submarine area of the bay at a scale 1:5000 was carried out. Additionally the stratigraphy of the late Holocene sediments was studied and micropaleontological and palynological study of collected samples from the deposits of the coastal alluvial plain as well as radiocarbon dating of selected layers rich in organic material were done. The main morphological features of the coastal zone are two beachrock formations with the first one extending along the coastline reaching a depth of-1.70 m and the second one occupying the southern part of the bay lying between -1.90 and -2.90 m below sea level. Microfaunal and palynological analysis of collected samples identified two main sedimentary sequences. The uppermost sedimentary unit represents a terrestrial depositional environment dominated by aeolian wellsorted sands and fluvial sediments. The underlying sequence showed a lagoonal depositional environment, implying a protected lagoon connected to the sea, which was periodically supplied with fresh water. This lagoon existed between 3700 years BP and 700 years BP as radiocarbon dating showed. The existence of this lagoon after that period is possible.